SOCIAL PROCESSES OF STUDENTS' INTELLECTUAL CULTURE DEVELOPMENT IN THE STUDY OF OUR NATIONAL CULTURAL HERITAGE (Scientific journal of the Fergana State University, 2023)
In the article have been explored final targets of modern education, the issues of breading professional as a fully developed person. The ultimate goal of modern teaching in an educational institution is depends of social needs of the specialist focused on socio-economic requirements. There are considered basic approaches to the formation of students' intellectual culture.